A novel PCR assay and sampling techniques for the detection of Raillietiella orientalis - Palmisano, Jenna N.; Hazelrig, Corinna M.; Gazil, Jack A.; Hanco, Jennifer K.; Farrell, Terence M.; Bogan, James E.; Nemeth, Nicole M.; Savage, Anna E. (Frontiers in Amphibian and Reptile Science, 2025)
Raillietiella orientalis, an invasive crustacean pentastome parasite, threatens native snake populations in the southeastern United States, infecting at least 18 species across Florida. Pentastome parasites have complex life cycles, with snakes often serving as definitive hosts for adult parasites that attach to the lungs and shed eggs into the host feces. PCR assays exist that distinguish invertebrate species via amplification and sequencing of mitochondrial DNA fragments. However, no molecular assays specific for R. orientalis or optimized fecal flotation methods for pentastome egg detection are available. We developed a novel PCR assay targeting the R. orientalis cytochrome c oxidase subunit I (CO1) gene and validated it across 611 samples, including cloacal swabs and fecal samples from live and deceased snakes, multiple pentastome species, and confirmed positive and negative control snakes diagnosed from lung dissections, morphology, and sequencing. We also compared the wet mount microscopy and three fecal flotation techniques for egg detection and assessed the impact of aging and drying on the fecal sample effectiveness. Our PCR assay demonstrated 100% specificity for R. orientalis across all sample types with 98% sensitivity for R. orientalis adults, larvae, and eggs (feces). The lowest sensitivity was observed in cloacal swabs (22%). The PCR assay was tested in a separate laboratory with similar results. Wet mount microscopy was more effective than fecal flotation for egg counts, though the false negative rate did not differ significantly between methods. Aging feces reduced egg counts but did not significantly increase the number of false negatives. Based on these results, we recommend using fecal samples from live snakes as the primary detection method, supplemented by cloacal swabs. These optimized methods are critical for improving surveillance of R. orientalis and characterizing the threat of this invasive pentastome to native snake species in the southeastern United States.